(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Poetry is an exciting rhythmic speech, arranged in a certain order in terms of melody, as an expression of emotions. Rhythm (consistent and uniform repetition of similar small passages) and rhyme (melodic words at the end of verses) are a certain means of regulating the poetic speech in terms of tone. When reading a poem, it is important that young students are excited by the poetic depiction of natural and social events. In the primary grades, stories, fairy tales, ie poems and lyrical poems written in the form of poems are taught.